Processes of tribal unification and integration - Doshi, S.L. (Delhi, 1978)
POLITICAL unification of the Bhils is a redhot subject for the anthropologists. Political unification includes all political processes which deal with the distribution of power and authority for the attainment of national goal. The conditions laid down by the national goals form the national mainstream or the comprehensive national culture. Before any attempt is made to analyse the unification processes in Indian society, particularly in disadvantaged groups such as the scheduled tribes, it is essential to clarify the meaning of the term "political".
Keywords: India Scheduled tribes